Understanding the Power of Law: Engaging Students in Criminal Law Casework - Heather Douglas; Monica Taylor (Legal Education Review)
This article considers the embedding of the ‘Ethics and Professional Responsibility’ graduate attribute into two subjects at the Faculty of Law, University of Technology Sydney: Ethics and Professional Conduct, and Evidence and Criminal Procedure. The focus is on an aspect of how law students are taught to ‘think like a lawyer’ and make legal decisions that require ethical judgment specifically narrative intelligence and the emotional content of ethical judgment. The content of two teaching and learning strategies that incorporate emotional knowledge will be explained. The purpose of the strategy in Ethics and Professional Conduct is to equip students with an understanding of the impact of emotions on ethical judgment and the need for emotional self-awareness. The purpose of the strategy in Evidence and Criminal Procedure is to equip students with an understanding of the ethical implications of how lawyers use emotion persuasively and tactically to influence juror judgment. Cognitive philosophy is applied in these strategies to exhibit how emotion within narratives can be the subject of analysis and how lawyers use emotion to influence juror decisionmaking and whether, and in what circumstances, this is ethical.